2017
DOI: 10.3892/ijo.2017.4155
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-20b promotes cell proliferation via targeting of TGF-β receptor II and upregulates MYC expression in Ewing's sarcoma cells

Abstract: Transforming growth factor-β receptor II (TGFBR2) is implicated in various types of cancer. Most molecules involved in the TGF-β pathway can be degraded by one or more microRNAs (miRNAs). In the present study, we show that miRNA plays an important role in downregulating TGFBR2 expression in Ewing's sarcoma (ES) cells. Microarray-based analyses revealed that the expression of miR-20b was significantly increased, whereas TGFBR2 and MYC were significantly downregulated and upregulated, respectively, in all ES cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 23 publications
3
13
0
Order By: Relevance
“…The KEGG enrichment analysis in the present study revealed that the identified DEGs were enriched primarily in cancer-associated pathways and the PI3K-Akt signaling pathway. Earlier studies have reported that the PI3K-Akt signaling pathway participates in the proliferation, invasion and migration of tumor cells, and these results support those of the present study (24,25). A PPI network was constructed for the identified DEGs, and the most significant module was subsequently extracted from the PPI network.…”
Section: Discussionsupporting
confidence: 94%
“…The KEGG enrichment analysis in the present study revealed that the identified DEGs were enriched primarily in cancer-associated pathways and the PI3K-Akt signaling pathway. Earlier studies have reported that the PI3K-Akt signaling pathway participates in the proliferation, invasion and migration of tumor cells, and these results support those of the present study (24,25). A PPI network was constructed for the identified DEGs, and the most significant module was subsequently extracted from the PPI network.…”
Section: Discussionsupporting
confidence: 94%
“…Using loss-of-function experiments we revealed that miR-20b inhibits proliferation and colony formation abilities, reduces viability, and increases ratio of early apoptotic cells in GC cell lines. These results confirm that miR-20b is highly pronounced as oncogenic, driving cellular processes such as cancer cells proliferation [20] and colony formation [31], invasiveness and tumor growth [19]. Our study is the first which investigates the functional importance of miR-20b in gastric carcinogenesis, GC cell lines, and the GC mouse model INS-GAS.…”
Section: Discussionsupporting
confidence: 81%
“…Here, we chose to analyze two miRNAs, miR-20b and miR-451a, shown to be deregulated in many different malignancies, including GC [13][14][15][16][17]. Previous functional studies have revealed that these miRNAs may exert their biological role through mediating tumor formation, maintenance, and metastasis [18][19][20][21]. However, the role of these miRNAs and possible target genes in GC remain poorly investigated.…”
Section: Introductionmentioning
confidence: 99%
“…It is demonstrated that the aberrant miRNAs expression profiles are involved in tumor initiation, progression and metastasis, including Ewing’s sarcoma. 6 10 Recent studies have proved that various miRNAs have the potential to be a biomarker or target for tumor progression, prognosis, and therapy. 11 14 These findings suggest that miRNAs provide a novel area for the research of progression, metastasis and therapy of Ewing’s sarcoma.…”
Section: Introductionmentioning
confidence: 99%